Sublingual sugar for hypoglycaemia in children with severe malaria: a pilot clinical study. - Graz, B; Dicko, M; Willcox, M; Lambert, B; Falquet, J; Forster, M; Giani, S; Diakite, C; Dembele, E; Diallo, D; Barennes, H (BioMed Central, 2008)
BACKGROUND: Hypoglycaemia is a poor prognostic indicator in severe malaria. Intravenous infusions are rarely feasible in rural areas. The efficacy of sublingual sugar (SLS) was assessed in a pilot randomized controlled trial among hypoglycaemic children with severe malaria in Mali. METHODS: Of 151 patients with presumed severe malaria, 23 children with blood glucose concentrations < 60 mg/dl (< 3.3 mmol/l) were assigned randomly to receive either intravenous 10% glucose (IVG; n = 9) or sublingual sugar (SLS; n = 14). In SLS, a teaspoon of sugar, moistened with a few drops of water, was gently placed under the tongue every 20 minutes. The child was put in the recovery position. Blood glucose concentration (BGC) was measured every 5-10 minutes for the first hour. All children were treated for malaria with intramuscular artemether. The primary outcome measure was treatment response, defined as reaching a BGC of >or= 3.3 mmol/l (60 mg/dl) within 40 minutes after admission. Secondary outcome measures were early treatment response at 20 minutes, relapse (early and late), maximal BGC gain (CGmax), and treatment delay. RESULTS: There was no significant difference between the groups in the primary outcome measure. Treatment response occurred in 71% and 67% for SLS and IVG, respectively. Among the responders, relapses occurred in 30% on SLS at 40 minutes and in 17% on IVG at 20 minutes. There was one fatality in each group. Treatment failures in the SLS group were related to children with clenched teeth or swallowing the sugar, whereas in the IVG group, they were due to unavoidable delays in beginning an infusion (median time 17.5 min (range 3-40).Among SLS, the BGC increase was rapid among the nine patients who really kept the sugar sublingually. All but one increased their BGC by 10 minutes with a mean gain of 44 mg/dl (95%CI: 20.5-63.4). CONCLUSION: Sublingual sugar appears to be a child-friendly, well-tolerated and effective promising method of raising blood glucose in severely ill children. More frequent repeated doses are needed to prevent relapse. Children should be monitored for early swallowing which leads to delayed absorption, and in this case another dose of sugar should be given. Sublingual sugar could be proposed as an immediate "first aid" measure while awaiting intravenous glucose. In many cases it may avert the need for intravenous glucose.